Praktik Black Market Pada Transaksi Iphone Ex-Inter Ditinjau Dari Hukum Perlindungan Konsumen - Ni Luh Putu Novita Sari; Dewa Gede Pradnya Yustiawan (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Small-scale retail is an economic business that stands alone with capital and is carried out by people who sell Consumer legal protection for the community is very important. Therefore, a synergistic relationship between consumers, employers and the government is needed to realize the performance of customer safety in society. The reason of writing on this thesis includes a standard objective, particularly to meet one of the necessities and duties of finishing a examine to gain a Bachelor of Laws diploma on the Faculty of Law, Udayana University and a particular objective, particularly to recognize and recognize the shape of criminal safety for purchasers in shopping for and promoting transactions of iPhone ex-inter. experiencing IMEI blocking. The approach utilized in scripting this thesis is a normative juridical writing approach that applies the ideas of fantastic law, in scripting this thesis numerous procedures are used, particularly the statutory method and the conceptual method. The conclusions drawn from this writing are First, the shape of criminal safety that may be acquired with the aid of using purchasers is that it is able to be withinside the shape of preventive criminal safety according with Article four of the Consumer Protection Act which regulates customer rights and is achieved earlier than a contravention occurs.